Footsie, Yeah! Share Prices and Worker Wellbeing - Alex Bryson; Andrew E. Clark; Colin P. Green (Institute of Labor Economics (IZA), 2021)
A small literature has shown that individual wellbeing varies with the price of company stock, but it is unclear whether this is due to wealth effects among those holding stock, or more general effects on sentiment, with individuals taking rising stock prices as an indicator of improvements in the economy. We contribute to this literature by using two data sets to establish the relationship between share prices on the one hand and worker wellbeing on the other. First, we use data on share price movements and employee stock holding in a single corporation and provide suggestive evidence that an increase in the firm's stock price increases the wellbeing of those who belong to its employee share purchase plan (ESPP), and that these effects are greatest among those making the largest monthly contributions to the program who have the most to gain (or lose) from stock price fluctuations. There is also some tentative evidence that the wellbeing effects of a rise in the share price are greatest among those with the largest shareholdings. We then use almost 30 years of British panel data to show that employee job satisfaction moves with share prices among those whose pay is partly determined by company fortunes. Taken together these results suggest that the well-being effects of share prices work at least partly via changes in wealth.
Keywords: J28; J33; J54; J63; J81; M52; 330; job satisfaction; wellbeing; share prices; share ownership; profit-sharing